Використання комп’ютерного тезауруса в дослідженні мови поетів - Васильєва, І. (Лексикографічний бюлетень, 2006)
In our research we propose the ways for using computer-based Ukrainian thesaurus and the
frequency dictionary of Ukrainian poetry for creating poetry language picture. We consider
lexico-semantical group "Human" in Ukrainian poetry discourse of 90-th.